Quackery is still rampant - Haque, Anwar Ul (International Journal of Pathology, 2018)
Quackery is an unscientific, unproven and non established method of patient management. It may or may not have ulterior motives! If there are ulterior motives then it also constitutes a fraud! Quackery had been in practice all over the world since time immemorial. First documented evidence of effective check on Quackery is by Abbasi Khalifa Walid who is also known to have built first modern hospital about 1300 years back